The assessment in terms of QBO of NeQuick 2 model - Sağır, S.; Atıcı R.; Akalın Y.; Yeşil A. (Elsevier B.V., 2019)
The NeQuick 2 model which is a model calculated to ionospheric parameter was evaluated in terms of the stratospheric QBO. The relationship with QBO of the difference (?NmF1) was investigated by the multiple regression analysis model. ?NmF1 defined as the difference (?NmF1 = NmF1measured ? NmF1NeQuick 2) between the measured value from ionosonde and calculated value through the NeQuick 2 model of maximum electron density of the F1 region (NmF1). This investigation showed that the relationship at solar maximum case is stronger than the relationship at solar minimum case both in Darwin and in Learmonth stations. In solar minimum case, there are negative correlations between QBO and ?NmF1 at both stations. In Darwin station, 67% of ?NmF1 changes in case of solar maximum, 35% of ?NmF1 changes in case of solar minimum can arise from the QBO. In Learmonth station, 51% of ?NmF1 changes in case of solar maximum, 30% of ?NmF1 changes in case of solar minimum can arise from the QBO. The results showed that the addition of QBO to the NeQuick 2 model would allow making calculations closing to actual data especially in the equator region of this model. © 2018 National Authority for Remote Sensing and Space Sciences
Keywords: Electron density; Ionospheric F1 region; NeQuick 2 Model; QBO